Evaluasi Rekrutmen Panitia Pengawas Pemilihan Umum Kecamatan Di Badan Pengawas Pemilihan Umum Kabupaten Lahat - Saswita, Saswita; Fansyah, Andi Joni; Idi, Abdullah (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
This study was to determine the Evaluation of the Recruitment of the Sub-district Election Supervisory Committee at the General Election Supervisory Agency of Lahat Regency. The results of this study are expected to be used as study material to develop public administration science, especially for academics regarding the Recruitment of the Subdistrict Election Supervisory Committee at the Lahat Regency General Election Supervisory Agency, academic institutions, as scientific information to develop science, technology and conduct further research and can motivate writers to learn a lot and to understand human resource management, add insight and knowledge for writers about the Recruitment Activities of the Sub-district Election Supervisory Committee at the Lahat Regency General Election Supervisory Body. The conclusions of this study are as follows: (1). The Recruitment Activities of the Subdistrict Election Supervisory Committee At the General Election Supervisory Body of Lahat Regency, it has been going well but for existing human resources to always be empowered in every activity, then for the selection stage it is added with a health test conducted by the Regency/City Bawaslu, not only it is only an administrative requirement by attaching a health letter, but a strict medical examination must be carried out, but from another point of view it is felt to be good and meet the standards that have been determined and set. (2). The Recruitment Factors for the Sub-district Election Supervisory Committee (Panwascam) are: a). The understanding of the staff and candidates for Panwascam about the implementation of the Recruitment of the Sub-district Election Oversight Committee at the General Election Supervisory Agency of Lahat Regency is still lacking, sometimes they think that this selection process is just a formality, presumably to be removed from their minds, because this selection process is important for determine the quality of election organizers at the district level with good quality and integrity. b). The lack of existing staff and supporting facilities will make the recruitment process and mechanism a bit disrupted.